Tissue factor as a link between inflammation and coagulation - Witkowski, Marco; Landmesser, Ulf; Rauch, Ursula (Trends in cardiovascular medicine, 2016)
Due to its receptor activity for factor VII, tissue factor (TF) is primary initiator of the blood coagulation cascade and ensures rapid hemostasis in case of organ damage. Inflammatory cytokines, such as tumor necrosis factor-α or interleukins, strongly induce expression of both full-length TF as well as the alternatively spliced TF in endothelial and blood cells. Beyond its role in hemostasis, TF also has signaling activity and promotes pleiotropic inflammatory responses via protease-activated receptors in concert with other coagulation factors. Alteration of TF expression and TF alternative splicing provides an effective means to change the endothelial phenotype and modulate inflammatory responses of the vessel.